2015
DOI: 10.1007/s12155-015-9669-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Lignin Fractions on Saccharification Efficiency in Diverse Species of the Bioenergy Crop Miscanthus

Abstract: Lignin is a key factor limiting saccharification of lignocellulosic feedstocks. In this comparative study, various lignin methods-including acetyl bromide lignin (ABL), acid detergent lignin (ADL), Klason lignin (KL), and modified ADL and KL determination methods-were evaluated for their potential to assess saccharification efficiency. Six diverse accessions of the bioenergy crop miscanthus were used for this analysis, which included accessions of Miscanthus sinensis, Miscanthus sacchariflorus, and hybrid spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
(72 reference statements)
3
39
2
Order By: Relevance
“…However, the average value of the lignin found in this study (2.6%) was lower than the values recorded for some lingocellulosic biomasses that exhibit a potential for the production of second generation ethanol, such as wheat straw, with 13 to 15% lignin, and bagasse from sugarcane, containing 23 to 32% lignin (Saini et al, 2015). Lignin is a key limiting factor in the saccharification of lignocellulosic feedstocks (Van der Weijde et al, 2016).…”
Section: Resultscontrasting
confidence: 73%
“…However, the average value of the lignin found in this study (2.6%) was lower than the values recorded for some lingocellulosic biomasses that exhibit a potential for the production of second generation ethanol, such as wheat straw, with 13 to 15% lignin, and bagasse from sugarcane, containing 23 to 32% lignin (Saini et al, 2015). Lignin is a key limiting factor in the saccharification of lignocellulosic feedstocks (Van der Weijde et al, 2016).…”
Section: Resultscontrasting
confidence: 73%
“…It was previously shown that OPM-9 ( M . × giganteus ), the most widely exploited miscanthus variety, has a considerably lower quality for biofuel production compared to many other accessions (van der Weijde et al, 2016a), which is shown here to be the case across diverse environments.…”
Section: Resultsmentioning
confidence: 50%
“…Saccharification efficiency of the samples was assessed by the conversion of cellulose into glucose and hemicelluloses into xylose using a mild alkaline pretreatment and enzymatic saccharification reaction, essentially as described by van der Weijde et al (2016a). Reactions were carried out in triplicate using 500 mg subsamples per stem sample.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in accuracy of reference wet chemical procedures used to obtain ADL and LIG, and in the magnitude of their concentrations, have been observed by others [29,[60][61][62]. While both are Klason lignin procedures, LIG determination involves an additional acid hydrolysis step in an autoclave and the ADL procedure may not retain all lignin components [63]. There were no differences between switchgrass cultivars for biomass compositional traits (Table 5), but miscanthus lines differed in concentrations of both forms of ash and lignin.…”
Section: Biomass Composition According To Differing Nirs Prediction Mmentioning
confidence: 97%